2015
DOI: 10.1124/dmd.115.063545
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Quantification of Hepatic Drug Processing Genes in Germ-Free Mice

Abstract: Intestinal bacteria have been shown to be important in regulating host intermediary metabolism and contributing to obesity. However, relatively less is known about the effect of intestinal bacteria on the expression of hepatic drug-processing genes in the host. This study characterizes the expression of hepatic drug-processing genes in germ-free (GF) mice using RNA-Seq. Total RNA were isolated from the livers of adult male conventional and GF C57BL/6J mice (n = 3 per group). In the livers of GF mice, the mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 19 publications
(22 reference statements)
9
73
2
1
Order By: Relevance
“…There are certain genes for which the mRNAs are moderately altered in livers of GF mice in a previous RNA sequencing (RNA-Seq) (Selwyn et al, 2015b), but were not altered in livers of GF mice the present study (such as Ces2a,Akr1c19,Cyp2b10,Cyp3a16,etc.). This inconsistency is likely due to different techniques used (RNA-Seq versus reversetranscription qPCR), vehicle effects, and/or statistical methods.…”
Section: Discussionmentioning
confidence: 87%
“…There are certain genes for which the mRNAs are moderately altered in livers of GF mice in a previous RNA sequencing (RNA-Seq) (Selwyn et al, 2015b), but were not altered in livers of GF mice the present study (such as Ces2a,Akr1c19,Cyp2b10,Cyp3a16,etc.). This inconsistency is likely due to different techniques used (RNA-Seq versus reversetranscription qPCR), vehicle effects, and/or statistical methods.…”
Section: Discussionmentioning
confidence: 87%
“…Quantification of the mRNA in conventional and germ-free mice indicates that 21 drug-processing genes were increased, and 34 were decreased by the germ-free condition. Probably the most important findings are that the level of mRNA encoding Cyp3a in the germ-free mice is much lower, and the level of mRNA encoding Cyp4a is much higher in livers of germ-free mice (Selwyn et al, 2015) (Fig. 15).…”
Section: Intestinal Microbiota Affects Host Drug Metabolismmentioning
confidence: 96%
“…Comparisons of the expression of the mRNAs of these drugprocessing genes in conventional and germ-free mice have been reported (Bjorkholm et al, 2009;Toda et al, 2009;Selwyn et al, 2015). Quantification of the mRNA in conventional and germ-free mice indicates that 21 drug-processing genes were increased, and 34 were decreased by the germ-free condition.…”
Section: Intestinal Microbiota Affects Host Drug Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated differential expression of xenobiotic metabolism in livers of germ-free or conventionally raised mice demonstrating that microbial metabolites of tryptophan act as aryl hydrocarbon receptor (AHR) activators (Selwyn et al, 2015).…”
Section: Et Vous Excrétion?mentioning
confidence: 99%